2011
DOI: 10.3109/15563650.2011.585429
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring trends in dextromethorphan abuse using the National Poison Data System: 2000–2010

Abstract: The increasing trend of DXM abuse cases noted in the first half of the decade by previous studies seems to have peaked at 17.6 calls per million population in 2006. It is likely that a combination of legislative, educational, and economic initiatives are responsible for the observed plateau.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 17 publications
1
36
0
Order By: Relevance
“…The risks may be analogous to the NMDA receptor antagonist dextromethorphan. Dextromethorphan is dispensed widely as a cough suppressant despite concerns related to its abuse liability (58) and psychotigenic potential (59). …”
Section: Nmda Receptor Antagonists As Rapid-acting Antidepressantsmentioning
confidence: 99%
“…The risks may be analogous to the NMDA receptor antagonist dextromethorphan. Dextromethorphan is dispensed widely as a cough suppressant despite concerns related to its abuse liability (58) and psychotigenic potential (59). …”
Section: Nmda Receptor Antagonists As Rapid-acting Antidepressantsmentioning
confidence: 99%
“…23 Emerging in popularity in the early 2000s, 24 a15-fold increase in dextromethorphan abuse-related calls in children aged 9 to 17 years was noted from 1999 to 2004. 25 A 2010 survey reported that 5.9% of high school seniors previously abused dextromethorphan, 26 and a 2012 survey indicated that 4.4% of American high school students abused cough or cold medications in the previous year. 3 In 2004, the American Medical Association released a warning regarding dextromethorphan misuse and recommended restrictions on its OTC use.…”
Section: Discussionmentioning
confidence: 99%
“…Recreational intake of DXM has been documented in case reports of adolescents and young adults in the United States, Germany, Thailand, and Iran (Chomchai and Manaboriboon 2012;Murray and Brewerton 1993;Mutschler et al 2010;Price and Lebel 2000;Wolfe and Caravati 1995;Ziaee et al 2005), in large-scale surveys of students in the United States (Falck et al 2006(Falck et al , 2012Johnston et al 2011), and examination of poison control, emergency room, and criminal cases (Banerji and Anderson 2001;Logan et al 2009Logan et al , 2012Wilson et al 2011). The growing need for awareness by medical practitioners of the symptoms of DXM overdose has also been noted, particularly due to the risk of associated psychiatric and central nervous system consequences (Alam, Nelson, and Bastiampillai 2013;Haroz and Greenberg 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Significantly, current use of DXM and hallucinogens was at least 10% in a subsample of eleventh-and twelfth-grade students who scored highest on a measure of problematic substance abuse (Falck et al 2012). Rates of DXM misuse reported to poison control centers have increased in frequency in recent years in Texas (Forrester 2011), California (Bryner et al 2006), and on a national level (Wilson et al 2011), with the highest frequency of abuse occurring among adolescents aged 15 and 16 (Bryner et al 2006). In the United States, non-medical DXM use accounted for 35% of the DXM-related emergency department visits, with 51% of such visits occurring in those aged 12 to 20 (SAMHSA 2008).…”
Section: Introductionmentioning
confidence: 94%